Developmental competence and antigen switch frequency can be uncoupled in Trypanosoma brucei - McWilliam, Kirsty R. (Proc Natl Acad Sci U S A, 2019)
African trypanosomes use an extreme form of antigenic variation to evade host immunity, involving the switching of expressed variant surface glycoproteins by a stochastic and parasite-intrinsic process. Parasite development in the mammalian host is another feature of the infection dynamic, with trypanosomes undergoing quorum sensing (QS)-dependent differentiation between proliferative slender forms and arrested, transmissible, stumpy forms. Longstanding experimental studies have suggested that the frequency of antigenic variation and transmissibility may be linked, antigen switching being higher in developmentally competent, fly-transmissible, parasites (“pleomorphs”) than in serially passaged “monomorphic” lines that cannot transmit through flies. Here, we have directly tested this tenet of the infection dynamic by using 2 experimental systems to reduce pleomorphism. Firstly, lines were generated that inducibly lose developmental capacity through RNAi-mediated silencing of the QS signaling machinery (“inducible monomorphs”). Secondly, de novo lines were derived that have lost the capacity for stumpy formation by serial passage (“selected monomorphs”) and analyzed for their antigenic variation in comparison to isogenic preselected populations. Analysis of both inducible and selected monomorphs has established that antigen switch frequency and developmental capacity are independently selected traits. This generates the potential for diverse infection dynamics in different parasite populations where the rate of antigenic switching and transmission competence are uncoupled. Further, this may support the evolution, maintenance, and spread of important trypanosome variants such as Trypanosoma brucei evansi that exploit mechanical transmission.